PENERAPAN METODE PROYEK UNTUK MENINGKATKAN KREATIVITAS DAN MOTORIK HALUS (Studi Pada Anak Kelompok B TK Negeri 3 Bengkulu Selatan) - Rita Yuliani; Bambang Sahono (DIADIK, 2020)
The purpose of this study was to describe the application of the project method in increasing children's creativity and fine motor skills and to describe the effectiveness of the application of the project method in improving the fine motor skills of group B in TK Negeri 3 Bengkulu Selatan. This research method is classroom action research (CAR) and quasi experiment. The subjects of this study were group B1 for the CAR class, B2 in the experimental class and B3 for the control class. Data collection techniques used teacher observation sheets, creativity observation and fine motor observation. The data analysis technique used is the paired and independent two-sample t test. The results of the t-test analysis showed that the t count was greater than the t table, which means that there was a significant difference in the average assessment of children's creativity and fine motor skills in each cycle. The results showed that the application of the project method can improve creativity and fine motor skills of children in group B TK Negeri 3 Bengkulu Selatan.